Evaluation and characterization of spider venom for controlling blow fly, Chrysomya megacephala fabricius (Diptera: Calliphoridae) - Saw, Siew Fen (2018)
Blow fly (Chrysomya megacephala) is a well-known cosmopolitan pest in most poultry farms. In Malaysia, an unpublished data of spider species Leucauge sp. and Pardosa sp. have shown insecticidal activity against the larvae of Spodoptera litura and Spodoptera exigua. However, their potential use in controlling C. megacephala is unknown. Hence, the objectives of this study were to evaluate the insecticidal activity of spider venom(s) against C. megacephala as well as to characterize and evaluate the spider toxin(s) with potential insecticidal activity. The spider venoms were extracted from the field collected spiders, precipitated and fractionated by HPLC. The crude venom of Pardosa sp. did not induce mortality in maggots but the crude venom of Leucauge sp. had caused 100% mortality towards the maggots. The lethal dosage (LD50) value of both crude venom and partial purified venom of Leucauge sp. was 38.92 and 33.19 μg/g, respectively. The SDSPAGE results had revealed that protein bands of supernatant of partial purified venom contained low molecular weight proteins (less than 11 kDa). Three HPLC purified fractions namely F7, F8 and F9 showed positive response to maggots with LD50 values of 1.61 μg/g, 2.33μg/g and 2.12 μg/g, respectively. The Q-TOF mass spectrometry analysis had confirmed these fractions fall into the class of disulfiderich neurotoxins and linear cytolytic peptides (1-10 kDa), within the toxicity range of the reported Ctenitoxin from Phoneutria nigriventer on Musca domestica. The potency test had confirmed negative response of Leucauge sp. venom towards Artemia salina which is a common organism used for toxicity test.